Selenium Resistant Bacilli and Pseudomonas as Potential Candidate for Selenium and Iron Biofortification in Maize Plants - Abadin , Zain Ul; Faisal, Muhammad (BioScientific Review, 2022)
Selenium is an essential element and is required in minute quantities for performing vital functions in living cells. Food is the ultimate source of selenium for animal and human populations. Crops, such as maize, which are used as food and feed, can be biofortified with selenium to alleviate selenium deficiency in both populations. The current study was conducted to isolate selenium-resistant bacteria from soil samples. Isolated bacteria were characterized on a morphological and biochemical basis. For specie level classification, 16S rRNA sequences were obtained. Isolated strains belonged to Bacillus halotolerans (TM3),Pseudomonas protegens (TM5), and Bacillus endophyticus (TM7). In-vitro PGPB characterization showed that some of the strains can produce IAA, Ammonia, HCN, and phosphate solubilization enzymes. Greenhouse pot experiments showed that the isolates enhanced seed germination rate, shoot length, and plant dry weight. Selenium supplementation caused decreased growth, but its effect was mitigated by the inoculation of isolated bacteria. Inoculation of these bacteria enhanced selenium content in maize leaves and shoots, ranging from 6-7%, while the addition of selenium to the soil increased selenium content by 300%. The iron content of maize leaves was also increased up to 17% in the inoculated strains.